Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 6 - Section 6.1 - Rational Expressions and Functions; Multiplying and Dividing - 6.1 Exercises: 56

Answer

$-(m+n)$

Work Step by Step

$\frac{m^{2}-n^{2}}{n-m}=\frac{(m+n)(m-n)}{n-m}=\frac{(m+n)(m-n)}{-(m-n)}=\frac{m+n}{-1}\times\frac{m-n}{m-n}=-(m+n)\times1=-(m+n)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.